Recognition or Ideology? The Dialogue between Axel Honneth and Louis Althusser Regarding the Sense of the Political Fight - Nación Pantigoso, Miguel Angel (2018)
The present article problematizes the notion of recognition in the thought of Axel Honneth, confronting it against the theory of ideology of Louis Althusser. If the struggle for recognition is the consequence of moral wrongs, the vindication of the values denied to the aggrieved is the objective. However, recognition posed in this way implies recognizing and subjecting the subject within a hegemonic value order. Only then, we can question whether the rupture or the reproduction of the ideological order indicates the limit of the critical potential of Honneth’s recognition theory. This article tries to answer this question.